Avaliação do pulso e pressão arteriais e do controle da dor utilizando-se dexametasona e cetorolaco como medicação pré-operatória em cirurgia de terceiros molares - Cardoso, Nayara Reis (2013)
The preemptive administration of anti-inflammatory drugs is performed in order to control the pain and swelling associated with extraction of impacted third molars. The aim of the study was to compare two anti-inflammatory a steroidal (dexamethasone 4 mg) and a non-steroidal (ketorolac tromethamine 10 mg) preoperatively of impacted third molars. Methodology: This research consists of a clinical trial, blinded, crossover paired, held at the Center for Health Sciences, Federal University of Espírito Santo, the Program of Postgraduate Dental Clinic, in patients enrolled in the discipline of Oral and Maxillofacial Surgery II. We selected 21 individuals of both sexes, aged 18 to 30 years old, healthy and lower third molars retained bilateral radiographically evaluated in a similar position. Two surgeries were performed by scholars of the eighth period and teachers responsible, separated by a minimum interval of 15 days. In the first procedure were administered one tablet of 10 mg ketorolac tromethamine, sublingually 1 hour before surgery. To third molar extraction of the opposite side was administered one tablet 4 mg of dexamethasone orally 1 hour before surgery. The anesthetic used was 2% lidocaine with 1:100,000 epinephrine. Pain was assessed by visual analog scales immediately after surgery, 6, 12, 24, 36, and 48 hours postoperatively. Systolic blood pressure (SBP) and diastolic (DBP) and pulse pressure were measured three times before the administration of drugs every 5 minutes for a mean baseline and every 15 minutes after administration, keeping the measurements throughout the surgical procedure . Results: There was no statistically significant difference for the variable pain, arterial pulse and SBP drugs. Comparing the times of the evaluation period 6 hours showed the highest levels of pain for both drugs. Dexamethasone did not alter the parameters evaluated, however, ketorolac caused a reduction of DBP after administration and therefore had lower mean DBP compared to dexamethasone. Conclusions: Dexamethasone 4 mg and ketorolac 10 mg operate effectively and similar in the control of pain after removal of third molars and are safe within the parameters evaluated. By providing DBP reduction, ketorolac is indicated for patients eager for anxiolytic and sedative inherent to the drug.